22Ne and 23Na ejecta from intermediate-mass stars: the impact of the new LUNA rate for 22Ne(p, γ)23Na. Issue 4 (29th November 2016) - Slemer, A.; Marigo, P.; Piatti, D.; Aliotta, M.; Bemmerer, D.; Best, A.; Boeltzig, A.; Bressan, A.; Broggini, C.; Bruno, C. G.; Caciolli, A.; Cavanna, F.; et al.
Abstract: We investigate the impact of the new LUNA rate for the nuclear reaction 22 Ne( p, γ) 23 Na on the chemical ejecta of intermediate-mass stars, with particular focus on the thermally pulsing asymptotic giant branch (TP-AGB) stars that experience hot-bottom burning. To this aim, we use the PARSEC and COLIBRI codes to compute the complete evolution, from the pre-main sequence up to the termination of the TP-AGB phase, of a set of stellar models with initial masses in the range 3.0–6.0 M⊙ and metallicities Z i = 0.0005, 0.006 and 0.014. We find that the new LUNA measures have much reduced the nuclear uncertainties of the 22 Ne and 23 Na AGB ejecta that drop from factors of ≃10 to only a factor of few for the lowest metallicity models. Relying on the most recent estimations for the destruction rate of 23 Na, the uncertainties that still affect the 22 Ne and 23 Na AGB ejecta are mainly dominated by the evolutionary aspects (efficiency of mass-loss, third dredge-up, convection). Finally, we discuss how the LUNA results impact on the hypothesis that invokes massive AGB stars as the main agents of the observed O–Na anticorrelation in Galactic globular clusters. We derive quantitative indications on the efficiencies of key physical processes (mass-loss, third dredge-up, sodium destruction) in order to simultaneously reproduce both the Na-rich, O-poor extreme of the anticorrelation and the observational constraints on the CNO abundance. Results for the corresponding chemical ejecta are made publicly available.